2018
DOI: 10.3390/molecules23051021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils from Zingiberaceae Plants on Root-Rot Disease of Panax notoginseng

Abstract: Replanting obstacles of Panax notoginseng caused by complex factors, including pathogens, have received great attention. In this study, essential oils (EOs) from either Alpinia officinarum Hance or Amomum tsao-ko (Zingiberaceae) were found to inhibit the growth of P. notoginseng-associated pathogenic fungi in vitro. Subsequent GC-MS analysis revealed the chemical profiles of two plant derived EOs. Linalool and eucalyptol were found to be abundant in the EOs and tested for their antifungal activities. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…In the previous study, EOs from either Alpinia officinarum Hance and Amomum tsao-ko ( Zingiberaceae ) are found to have a good inhibition against the F. oxysporum , F. solani , and C. destrutans [26], and the EOs of Alpinia Katsumadai Hayata and Zingiber officinal Roscoe also have significant reductions in the mycelium growth of the pathogen in vitro [27]. This is corroborated by our findings.…”
Section: Discussionsupporting
confidence: 89%
“…In the previous study, EOs from either Alpinia officinarum Hance and Amomum tsao-ko ( Zingiberaceae ) are found to have a good inhibition against the F. oxysporum , F. solani , and C. destrutans [26], and the EOs of Alpinia Katsumadai Hayata and Zingiber officinal Roscoe also have significant reductions in the mycelium growth of the pathogen in vitro [27]. This is corroborated by our findings.…”
Section: Discussionsupporting
confidence: 89%
“…The A. katsumadai EO was found to be the most effective for inhibition of F. oxysporum with an IC 50 value of 21.86 mg mL −1 (Table 1 ). In addition, it has been reported that Amomum tsao-ko also displays an inhibitory effect on F. oxysporum (Sun et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned culturable microbes from rhizosphere soil were screened on the basis of their antagonistic activity against pathogens isolated from infected plants in a dual culture following the method described in a previous study with some modifications (Sun et al, 2018). A pathogen mycelium block (6 mm diameter) was placed in the middle of the Petri dish.…”
Section: Methodsmentioning
confidence: 99%